Investigating Nuisance Effects Induced in EEG During tACS Application - Holzmann, Romain; Koppehele-Gossel, Judith; Voss, Ursula; Klimke, Ansgar (Frontiers in Human Neuroscience, 2021)
Transcranial alternating-current stimulation (tACS) in the frequency range of 1–100 Hz has come to be used routinely in EEG studies of brain function through entrainment of neuronal oscillations. It turned out, however, to be highly non-trivial to remove the strong stimulation signal, including its harmonic and non-harmonic distortions, as well as various induced higher-order artifacts from the EEG data recorded during the stimulation. In this paper, we discuss some of the problems encountered and present methodological approaches aimed at overcoming them. To illustrate the mechanisms of artifact induction and the proposed removal strategies, we use data obtained with the help of a schematic demonstrator setup as well as human-subject data.